Refiguring Chaucer in the Renaissance - Krier, Theresa M., 1953- (University Press of Florida, 1998)
This collection of essays surveys the diverse receptions and workings of Chaucer from the early sixteenth to the early seventeenth century. It emphasizes the many kinds of influence that Chaucer and his poems exerted on British letters and culture during these years and assesses how "Chaucer"--Poet, works, and representations by others - became a cultural category that changed in Tudor and early Jacobean England, as the Reformation and increasing distance from Middle English made Chaucer representative of a lost medieval past